ANALISIS KESALAHAN PENGGUNAAN BAHASA DALAM PENULISAN TEKS EKSEMPLUM KARYA SISWA KELAS IX SMP LABORATURIUM UM - Yulina Mingvianita (FKIP, Universitas Palangka Raya, 2023)
Writing is not only a language skill, but writing can also be a means of activity to develop students' ability to use language. This is the cause of the importance of teaching skills in schools. The writing skill taught in class IX at SMP Laboratory UM is writing exemplum texts. Even though writing skills have been taught in class, there are still errors in the use of language in writing exemplary texts of students' work. This is due to the large number of students who think writing is difficult, so students pay less attention to accuracy and do not practice writing skills. One of the mistakes that often occur in punctuation marks is the use of capital letters, the use of abbreviations, the writing of prepositions (in, to, and, from), and waste in constructing sentences. The purpose of this article is to analyze errors in the use of written language by identifying, classifying, and systematically interpreting students' written language errors in text samples. The method used is a qualitative approach that describes and explains errors in the use of language in text writing samples through students' work.